Self-care in haemodialysis treatment tasks in community and hospital-based units: A cross-sectional study - Chava Kurtz; Efrat Shadmi; Karl Skorecki; Etty Kruzel-Davila; Alon Antebi; Tatyana Tsehovsky; Sivan Spitzer (PLoS ONE, 2025)
Background Patient self-care improves outcomes in chronic diseases, yet patients in haemodialysis units tend to be passive recipients of treatments. Purpose To explore patient self-care in haemodialysis tasks and identify factors influencing interest and participation. Methods Patient interest and participation were assessed using a Likert-type scale. Associations were tested with bi-variate analysis and logistic regression, accounting for hemodialysis unit type. Results Questionnaires from 339 patients in hospital and community-based units showed 89.1% expressed interest in care tasks. Lower education (OR 0.36, 95% CI 0.15–0.9) and being single (OR 0.27, 95% CI 0.12–0.6) decreased interest. Participation in treatment tasks was observed in 40.1% of patients. Lesser odds of participation were seen amongst those of Jewish religion (OR 0.3, 95% CI 0.02–0.54), and dialyzing in community units (OR 0.44, 95% CI 0.25–0.76), whereas higher odds were seen in people reporting higher economic status (OR 2.67, 95% CI 1.44–4.93), venous access via arteriovenous shunts (OR 3.31, 95% CI 1.98–5.54), more years on dialysis (OR 1.86, 95% CI 1.06–3.24), and participants expressing interest in participation (OR 6.01, 95% CI 2.18–16.53). A larger proportion of patients who were not interested in participation were from community-based units (75.7%), compared to those who expressed at least some interest (61%). Conclusions While most patients expressed interest in participating, only a minority actually participated. There is need for greater engagement of interested patients. Organizational factors play an important role in determining actual participation, above and beyond personal patient factors. Patients should be presented with the opportunity to participate according to their interest and capabilities.